1999
DOI: 10.1001/jama.281.12.1106
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome Following Gestational Exposure to Organic Solvents

Abstract: Contact me when this article is cited. This article has been cited 61 times. Topic collectionsContact me when new articles are published in these topic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
3
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 12 publications
(13 reference statements)
1
80
3
1
Order By: Relevance
“…Risks of low birth weights and fetal malformations have been reported to increase with work-related contact of pregnant women to benzene and other organic solvents (Khattak et al, 1999, Chen et al, 2000.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Risks of low birth weights and fetal malformations have been reported to increase with work-related contact of pregnant women to benzene and other organic solvents (Khattak et al, 1999, Chen et al, 2000.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Khattak S et al in a prospective study demonstrated that women exposed occupationally to organic solvents had a 13-fold risk of major malformations as well increased risk for miscarriages in previous pregnancies while working with organic solvents. (15) …”
Section: Organic Solventsmentioning
confidence: 99%
“…To our knowledge, this is the first study where the risk of congenital malformations in relation to occupational painting has been investigated by a register-based approach. Some previous studies have focused on maternal exposure to volatile organic compounds (VOC) and have shown an increased risk of congenital anomalies among the children (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%